Postoperative pain management in pediatric cleft lip and palate repair. Issue 4 (August 2021) - Flowers, Thomas; Winters, Ryan
Abstract : Purpose of review: There has been an increased interest in the literature on methods to improve perioperative outcomes in surgical patients while minimizing opioid use. Pediatric cleft palate repair can be a painful procedure, and this postoperative pain can lead to longer hospital stays and worse surgical outcomes. Recent findings: Recent literature has explored four key areas surrounding analgesia after cleft lip and palate repair. These areas are management of postoperative pain with nonopioid oral analgesics, peripheral nerve blockade, liposomal bupivacaine for donor-site analgesia in bone grafting, and enhanced recovery after surgery (ERAS) protocols. Summary: The included studies indicate that patients undergoing palatoplasty may have a decreased opioid requirement if nonopioid analgesics such as acetaminophen and ibuprofen are started early in the postoperative setting. Peripheral nerve blockade is an important adjunct to analgesia in these patients. Suprazygomatic maxillary nerve blockade may improve pain management over traditional infraorbital nerve blockade. In patients undergoing alveolar bone grafting, injection of liposomal bupivacaine into the donor site can significantly decrease oral opioid requirements. Finally, ERAS protocols are emerging ways to decrease postoperative pain in cleft palate patients.